(untitled) (Global Journal of Human-Social Science, 2024)
Spatial segregation in the West Bank remains a pressing issue with profound social economic and political implications This study examines the gap between the Palestinian Authority s PA political statements and the local implementation of strategic planning measures to counter segregation in Palestinian communities By analyzing the Strategic Development and Investment Plans SDIPs from 2018-2021 this research investigates the extent to which these plans address the challenges posed by Israeli settlements and promote inclusive urban development The findings reveal significant shortcomings including limited coverage of settlement-related challenges inadequate strategies to confront settlement activity and a lack of context-specific approaches Out of the 122 plans analyzed only 15 12 3 explicitly addressed the geopolitical situation while 67 54 9 acknowledged settlements as a challenge Disturbingly 28 plans 22 9 neglected the significance of Area C highlighting a substantial oversight Additionally 35 plans 28 7 considered Area C as inaccessible for development revealing an approach contrary to the official statements of the PA The absence of a clear vision for Area C and insufficient proposals for expansion and development exacerbate the issue To effectively address spatial segregation the PA must prioritize social and economic resilience formulate comprehensive strategic plans and enhance coordination between political statements and local planning practices This research underscores the urgency of integrated countersegregation measures emphasizing the importance of context-specific approaches and increased collaboration among stakeholders particularly in the coming SDIPs By bridging the gap between political statements and local implementation the PA can take tangible steps toward equitable sustainable and resilient spatial planning in the West Bank The methodology implemented in this research extends beyond spatial segregation in the West Bank providing a practical strategy to assess policy gaps in diverse situations particularly under uncertainties and restrictions offering valuable insights for policymakers and urban planners navigating complex challenges